Küreselleşme Kavramı Ve Küreselleşmeye Yönelik Yaklaşımlar - Kürkçü - Dumanlı, Duygu (The Turkish Online Journal of Design, Art and Communication, 2013)
The globalization is a notion which explains the very latest enhancements. Nonetheless it is not possible to reach to a concensus about the outcomes of globalization. In this study, we tried to explain notion of globalization and we analyzed the concepts of it. Then, we studied different approaches with the historical development of the concept.
Keywords: Globalization; Localization; Küreselleşme; Yerelleştirme